Promising Targets and Current Clinical Trials in Metastatic Non-Squamous NSCLC - Zer, Alona; Leighl, Natasha (Frontiers in Oncology, 2014)
Lung adenocarcinoma is the most rapidly increasing subtype of lung cancer today. With the discovery of EGFR mutations and ALK rearrangements and targeted therapy, personalized medicine has become a reality for patients with lung adenocarcinoma. Here we review potential additional targets and novel therapies of interest in lung adenocarcinoma including targets within the cell surface (receptor tyrosine kinases EGFR, HER2, RET, ROS1, MET, TRK), targets in intracellular pathways (ALK, RAS-RAF-MEK, PI3K-AKT-PTEN, WNT), nuclear targets such as PARP, HSP90 and histone deacetylase, and selected pathways in the tumour environment. With the evolving ability to identify specific molecular aberrations in patient tumours in routine practice, our ability to further personalize therapy in lung adenocarcinoma is rapidly expanding.